(untitled) (Лучшие интеллектуальные исследования, 2025)
The trade balance serves as a vital indicator of a country’s economic performance. Kyrgyzstan has consistently reported trade deficits, with imports outweighing exports. This study investigates the key determinants of Kyrgyzstan’s trade balance from 1993 to 2023, focusing on domestic GDP, external debt, remittances, and China’s GDP per capita—given China’s role as Kyrgyzstan’s largest trading partner. Employing the Ordinary Least Squares (OLS) model, the results reveal that Kyrgyzstan’s trade balance is negatively associated with domestic GDP and external debt, while positively influenced by remittance inflows and China’s GDP per capita.